Evaluasi Kinerja Alat Gali Muat Dan Alat Angkut Untuk Mencapai Target Produksi 25.000 Ton/Bulan Pada Penambangan Batu Kapur PT. Bakapindo Di Jorong Durian, Kenagarian Kamang, Kecamatan Kamang Magek, Kabupaten Agam, Sumatera Barat - Egivvano Iranda; Tri Gamela Saldy (Departemen Teknik Pertambangan FT UNP, 2021)
abstrack .This study aims to obtain an effort to increase the effective working time to achieve production targets and to obtain the need for loading and unloading equipment and transportation equipment needed to reduce waiting time by using queue theory at PT Bakapindo mining. Mining at PT Bakapindo is carried out using the quarry method, PT Bakapindo's production in May was 11837 tons/month and this did not meet the set target of 25,000 tons/month, digging tools used in PT Bakapindo 1 unit CAT 320 excavator and 2 units Mitsubishi Fuso 220 Ps, the productivity obtained from this tool is 15769.35 tons/month. By improving the efficiency of work time which can be increased to 84% and improving the composition of the tool, 1 unit of CAT 320 equipment can serve 3 units of Mitsubishi Fuso 220 Ps, so the productivity is 33028.67 tons/month. The results of this study indicate that the effective working time and working compatibility of mechanical tools are actually not maximized.